The Application of the Regression Method with Tree Structure on the Estimation of the Student Thesis Duration - Dewi, Theresia Trias Candra; Dewi, Yuliani Setia; Pradjaningsih, Agustina (Majalah Ilmiah Matematika dan Statistika, 2017)
The tree regression is one of the regresion methods that can be used to find out the influence of independent X variable to the dependent Y variable. The tree regression method analyzes data by doing step by step isolation. The prunning tree process is used in order to get the optimal tree size. Prunning tree is done based on cost complexity. This paper is written in order to apply the tree regression method in data of graduated student from Faculty of MIPA at 2001-2005 that used to find out the variable which has an influence to the long student minithesis. The research result shows that the long student minithesis is influenced by GPA and department.